Existing notions of conventional breeding metal whiskers, their analysis - Артемьев, Сергей Робленович (Eastern-European Journal of Enterprise Technologies, 2015)
The paper considers the existing views on the conventional methods of growing filamentary metal crystals, analyzes the kinetics of growing metal whiskers, examines disadvantages of various methods of producing this type of filamentary crystals, and studies their crystallization in the process of growing. Metal carbonyls, which are widely used in growing filamentary crystals, have been successfully used, particularly in metallurgy (in manufacturing metals and alloys), in chemical industry (in synthesizing organic compounds), in machine building (for obtaining protective and decorative coverings), etc. It proves that the industrial importance of carbonyls and metal carbonyls is constantly rising, which makes studies on growing the crystals in modern conditions rather topical. Meanwhile, it is obvious that so far studies on theoretical problems and practical application of metal carbonyls lack clear systematization. Our review of the studies has resulted in a clear understanding of the conventional methods of growing filamentary metal crystals. We have thoroughly analyzed the kinetics of growing metal whiskers, examined the current disadvantages of various methods of growing filamentary crystals, and studied the problems of their crystallization in the process of growing. The study findings can be conducive to improving the manufacture of products so that they could meet the requirements of environmental legislation, which will furthermore facilitate protection of man and environment from anthropogenic factors.